التربية بالعقوبة في ضوء الكتاب والسنة والنظريات الحديثة : دراسة تحليلية دراسة تحليلية - كعبي، خدية سالم محمد سعيد
This study aims to define the educational punishment in Islam and in Western approaches, along with the explanation of its resources both in Islam and Western approaches, and elucidation of its rulings in Quran and Sunnah. The study has employed inductive method to collect and track the topic of educational punishment stated in Hadith and in Islamic references, and in Western approaches. Furthermore, analytical method is applied to analyze the concept of Quran and Sunnah and concept of Western approaches regarding to the educational punishment. Also, the comparative method is used to observe the standards of Western morality and their comparison with the standards of Muslims morality prescribed in the Qur'an and Hadith. The most important findings of the study are that the rules of educational punishment in Islam which are stability, eternity, flexibility, and the antiquity of work with it and its application, has a great impact on the strength of the resulting influence on the individual and society to build personality, reform and control behavior, the sources of punishment in modern theories which are characterized by the continuous change accompanying the change of the human mind which is affected by the times and places in which it is found. The sources of educational punishment in Islam included an integrated educational curriculum in terms of comprehensive general rules upon which other similar rulings can be based. Thus, the Islamic educational curriculum has given flexibility in absorbing developments, and that the rules and regulation of modern educational punishment theories are constantly changing according to the change of human thought. And since it is variable, we find double resulting effect in educating society in form of punishment. This research recommended that educational centers and institutions, which work on examining the rules and regulation related to educational punishment that are taken from constitutions and modern systems and evaluate them according to the Islamic educational curriculum, the inappropriate ones should be subtracted, and research centers comprising the finest scholars and researchers should be established to study the Islamic educational curriculum and develop a comprehensive educational system through it.